The study of folk music in the modern world - Bohlman, Philip V., 1952- (Folkloristics., 1988)
""Bohlman examines folk music as a genre of folklore from a broadly cross-cultural perspective and espouses a more expansive view of folk music, stressing its vitality in non-Western cultures as well as Western, in the present as well as the past.""--Publisher's description